Cascudinhos do sul do Brasil: sistemática, endemismo e relações usando novas abordagens (Loricariidae: Hypoptopomatinae) - Delapieve, Maria Laura (2020)
Epactionotus and Eurycheilichthys are two genera of small catfishes with restricted distribution through the Southern Neotropical region. The two genera were the subject of a study provided by Reis & Schaefer (1998). With the discovery and description of new populations and species over the last 20 years, a new study was developed aiming at these two groups. Epactionotus species are known for inhabiting the rocky-bottom stretches of rivers in a limited geographic area along the Atlantic coast of southern Brazil. Distribution of each of the three species is endemic to single river drainage (except for E. bilineatus), being isolated from each other by the coastal lacustrine systems or the Atlantic Ocean. Epactionotus bilineatus is known from the rivers Maquiné and Três Forquilhas, both tributaries of the Tramandaí River System, while E. itaimbezinho is endemic to the Mampituba River drainage, and E. gracilis to the Araranguá River drainage. Most recently, new populations were revealed in other Atlantic coastal drainages of southern Brazil, more specifically, in the Urussanga, Tubarão, d’Una, and Biguaçu river drainages. Integrative species delimitation using molecular data (cytochrome oxidase subunit I - COI) and morphology (morphometrics and meristics) was applied in order to evaluate species recognition in isolated populations. In light of new data, the genus is re-diagnosed, the status of Epactionotus species/population is reevaluated, and the formerly described species are recognized. As for the newly discovered populations, the data strongly support only the population from the Biguaçu River drainage, in Santa Catarina State, as a new species and an independent lineage. Molecular and distributional data suggest that not only palaeodrainage connectivity can explain species distribution, but also, that strong per basin genetic structure may be related with species habitat specificity.As for Eurycheilichthys, the genus comprises nine species endemic and restrictedly distributed through two river basins in Southern Neotropical Region. The genus is better known by E. pantherinus, from the upper Uruguay River basin and E. limulus, from the upper reaches of the Jacuí River basin. The seven additional, and recently described, species of Eurycheilichthys, however, are all distributed through higher altitudes of the Taquari-Antas River basin, a tributary to the lower Jacuí River. Its diversity and endemism make Eurycheilichthys an important focal group for studying and understanding evolutionary biology. Phylogenomic analysis were carried out and interspecific genetic structure comparing rare and common polymorphisms were estimated from genomic data created for 65 individuals of the nine species using ddRADseq protocol, aiming to elucidate the relationships between the species and to provide a time divergence component. Analyses support Eurycheilichthys as a monophyletic genus comprising two species-inclusive clades, with absolute support and suggest two and very recently diverged lineages on the Taquari-Antas species. Except for Eurycheilichthys luisae, all remaining species were recovered as monophyletic. The more diverse lineages on the Taquari-Antas when compared to Uruguay and upper Jacuí River basins suggest a more dynamic landscape with several headwater capture events.